2022
DOI: 10.12659/ajcr.937397
|View full text |Cite
|
Sign up to set email alerts
|

Neuroleptic Sensitivity in Dementia with Lewy Body and Use of Pimavanserin in an Inpatient Setting: A Case Report

Abstract: Patient: Male, 75-year-old Final Diagnosis: Dementia with Lewy bodies Symptoms: Parkinsonism Medication:— Clinical Procedure: — Specialty: Neurology Objective: Unusual clinical course Background: Antidopaminergic medications, including antipsychotics, are known to worsen motor and neuropsychiatric symptoms, including cognition and psychosis, in patients with dementia with Lewy body (DLB). The intens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…This case adds to the growing body of literature demonstrating a favorable response to pimavanserin in LBD without the adverse effects experienced with other antipsychotics. Interestingly, both our patient and the one presented by Abadir et al showed worsening of symptoms when valproic acid was added for behavioral management [ 13 ]. What is unique about this case report, however, is the utilization of SAPS scoring, which provides invaluable information regarding specific psychotic symptoms and both how and when they responded to pimavanserin treatment.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This case adds to the growing body of literature demonstrating a favorable response to pimavanserin in LBD without the adverse effects experienced with other antipsychotics. Interestingly, both our patient and the one presented by Abadir et al showed worsening of symptoms when valproic acid was added for behavioral management [ 13 ]. What is unique about this case report, however, is the utilization of SAPS scoring, which provides invaluable information regarding specific psychotic symptoms and both how and when they responded to pimavanserin treatment.…”
Section: Discussionmentioning
confidence: 95%
“…Though there are some published randomized controlled studies demonstrating the efficacy of pimavanserin in the treatment of Alzheimer’s disease psychosis [ 11 , 12 ], to the best of the author's knowledge, only one other case report has been published demonstrating the potential benefits of pimavanserin sole use in LBD by Abadir et al [ 13 ]. This case adds to the growing body of literature demonstrating a favorable response to pimavanserin in LBD without the adverse effects experienced with other antipsychotics.…”
Section: Discussionmentioning
confidence: 99%
“…The extension of these therapies to patients with DLB is thus based on untested assumptions and may lead to efficacy or tolerability issues. For example, while preparing this review, we only found 1 manuscript that specifically focused only on DLB, a case report that described a patient with DLB whose hallucinations responded to pimavanserin but who discontinued it due to financial concerns (ie, the patient had a large copay); that patient subsequently experienced an increase in hallucinations while on clozapine and then returned to his baseline levels of psychosis when clozapine was discontinued and pimavanserin was reinitiated [ 26 ]. In addition, 4 retrospective medical record reviews, 1 case report, and 1 clinical trial included patients with DLB alongside other larger cohorts, but these publications did not report clear histories or specific findings on the patients with DLB.…”
Section: Discussionmentioning
confidence: 99%
“…Severe sensitivity to antipsychotic agents. Between 30% and 50% of patients with DLB have a sensitivity to antipsychotic drugs that is not dose-related 35. Antipsychotic medications also may worsen confusion or autonomic dysfunction.…”
Section: Supportive Clinical Featuresmentioning
confidence: 99%